Environmental effects of Amazonian storms on the weather of Ecuadorian coast - Marín Nieto, Luis (Revista Universidad de Guayaquil, 2013)
In 2008, 2012 and 2013 it were observed drastic climate changes in the Ecuadorian coast by storms from the headwaters of the Amazon River, on the eastern slopes of the Andes in the country is far less than 120 km from the Pacific, while scarce seasonal rains. This phenomenon is expressed by an overcast sky with gray clouds, continuous rain and less sunshine. During those years, extreme rainfall occurred in the southwest of Brazil on the Atlantic coast, as well as maximum levels in the Amazon River. This year also the phenomenon hit the Chocó (Colombia), Cajamarca (Perú), Cochabamba (Bolívia) and Rio de Janeiro, causing hundreds victims and material losses. This work is based on observation and hydrological records of Ecuador and Peru, in order to show an interpretation of the phenomenon, and invite the analysis of the event, meteorologists, hydrologists and environmentalists, and contribute to the need of a Weather Network Amazonian countries, covering the Pacific and the Atlantic coasts, to research and generate methodological models for preventing extreme droughts or floods, for greater oversight of deforestation and conservation of Amazonian biomass.